174k views
1 vote
Write the quadratic function in the form f (x)= a (x - h)' + k.
f (x) = 3x² - 6x+6

User Dragu
by
5.3k points

1 Answer

5 votes

Answer:


f(x) = 3(x - 1)^2-3

Explanation:

Given


f(x) = 3x^2 - 6x + 6

Required

Write as:


f(x) = a(x - h)^2 + k

In
f(x) = 3x^2 - 6x + 6, the coefficient of x is -6

Divide by 2: -3

Square: 9

Add 9 - 9 to the above equation


f(x) = 3x^2 - 6x +9-9+ 6

Split to 2


f(x) = [3x^2 - 6x +9]-[9- 6]


f(x) = [3x^2 - 6x +9]-[3]

Factorize:


f(x) = [3x^2 - 3x -3x+9]-[3]


f(x) = [3x(x - 1) -3(x-1)]-[3]


f(x) = [(3x - 3)(x-1)]-[3]

Factorize 3x - 3


f(x) = [3(x - 1)(x-1)]-[3]


f(x) = 3(x - 1)^2-[3]


f(x) = 3(x - 1)^2-3

User Bukso
by
5.3k points